PACKING STRATEGY: MODERNISASI UMKM JAMUR SANTRI - Kurnia Widya Oktarini; Meilinda Dwi Anugrah; devi febrianti; Ulfah Tika Saputri; Edy Firza (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2026)
The community service program was implemented to address the challenges faced by Pondok Jamur Santri, an MSME that had not yet applied an adequate packaging strategy, resulting in products with limited appeal and market value. This activity aimed to enhance the partner’s understanding and skills in applying an effective packing strategy, particularly through the use of environmentally friendly packaging, the development of a logo, and the preparation of product information in a more structured manner. The methods employed included field observation, needs analysis, participatory training, and assistance in creating packaging prototypes and visual identity designs. The results indicate an improvement in the partner’s ability to understand modern packaging concepts, as shown by the development of two packaging prototypes, several logo designs, and digital promotional materials. These outputs successfully addressed the partner’s needs and have the potential to strengthen the competitiveness of hydroponic products in the local market. Overall, this program demonstrates that implementing an appropriate packaging strategy can enhance business image and support the sustainability of MSMEs engaged in modern agricultural practices. Keywords: hydroponics, packaging strategy, MSME, product branding